Answers

2016-06-18T11:34:04+08:00
First, square (x+7). It would be:
(x+7)  ^{2} = x^{2} +14x+49=-3x
Then apply Addition Property of Equality, meaning add -3x to both sides of the equation.It will be: x^{2} +17x+49=0
. Then the standard form of the equation (x+7)(x+7)=-3x is  x^{2} +17x+49=0.
0
what is there value
If you mean the value of x, it would be hard to solve because the equation is not a perfect square. But if you mean the value of a, b, and c, a=1, b=17 and c=49.
that is what i mean
Not all quadratic equation can be solved by factoring. There are other 3 methods in addition to factoring to solve for the roots. In the above case, use quadratic formula which can be used to solve for the roots of any quadratic equation.
  • Brainly User
2016-06-18T14:59:11+08:00

(×+7)(×+7)=-3×

x2 + 7x + 7x + 49 + 3x = 0

x2 + 14x + 3x + 49  = 0

x2 + 17x + 49  = 0

a = 1;    b = 17;     c = 49

Solve using Quadratic Formula:

ANSWER:

x =  \frac{-17+ \sqrt{93}}{2}  and  \frac{-17- \sqrt{93} }{2}

PLEASE CLICK IMAGE BELOW TO VIEW SOLUTION USING QUADRATIC FORMULA.

0